Searches for electroweak production of charginos, neutralinos, and sleptons decaying to leptons and W, Z, and Higgs bosons in pp collisions at 8 TeV - CMS Collaboration; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V M; et al. (The European physical journal. C, Particles and fields, 2014)
Searches for the direct electroweak production of supersymmetric charginos, neutralinos, and sleptons in a variety of signatures with leptons and [Formula: see text], [Formula: see text], and Higgs bosons are presented. Results are based on a sample of proton-proton collision data collected at center-of-mass energy [Formula: see text] with the CMS detector in 2012, corresponding to an integrated luminosity of 19.5 [Formula: see text]. The observed event rates are in agreement with expectations from the standard model. These results probe charginos and neutralinos with masses up to 720 [Formula: see text], and sleptons up to 260 [Formula: see text], depending on the model details.